(untitled) (Caligrama: Revista de Estudos Românicos, 2019)
Resumo: Este artigo propõe-se analisar um dos gêneros mais produtivos da poesia palaciana portuguesa dos séculos XVI e XVII, o retrato elogioso da donna, de fundo petrarquista, largamente praticado no Quinhentos por poetas como Luís de Camões, Pero de Andrade Caminha e Sá de Miranda, e, no século seguinte, pelos poetas cujas obras foram reunidas nas coletâneas de verso Fênix Renascida e Postilhão de Apolo. Demonstra-se a prática de “notação” do retrato elogioso, discutem-se os preceitos retóricos e poéticos que o regravam, sua utilidade como controle dos afetos cortesãos, e como o seu contrário, o retrato cômico, especificamente aquele construído à base de metáforas de doce, valendo-se dos mesmos lugares comuns de invenção, disposição e elocução do gênero, articula a imagem reversa da donna, transformando a illustratio ou evidentia (de forte apelo visual), própria do retrato de tipo alto, em “apetite”, “gustação”, “gula” e “satisfação sexual”. Palavras-chave: sátira; retrato poético; elogio da donna; ars laudandi; Fênix Renascida. Abstract: This article proposes to analyze one of the most productive poetry genres of Portuguese palace in the 16th and 17th Centuries – praise of a lady, fundamentally Petrarchan, largely practiced in the 1500s by poets such as Luís de Camões, Pero de Andrade Caminha, and Sá de Miranda, and in the following century, by poets whose works were reunited in the collections of verses Phoenix Reborn (Fênix Renascida) and Apollo’s Postilion (Postilhão de Apolo). The practice of “Notation” in the complimentary portrait is demonstrated, the rhetorical and poetic precepts that are rewritten are discussed, its usefulness as a control on courtier affections as well as how its opposite, the comedic portrait, specifically that one built upon sweet metaphors, using the same commonplaces of invention, arrangement and elocution of the genre, articulates the reverse image of a lady, transforming the illustration or evidentia (of strong visual appeal), typical of the higher type portrait, into “appetite”, “gustation”, “gluttony”, and “sexual satisfaction”. Keywords: satire; poetic portrait; praise of a donna; ars laudandi; Phoenix Reborn.